Pemahaman Dalam Proses Pembuatan Bahan Dasar Konsentrat - Mustika, Indri Ayu; aminah, siti; Melinda, Vera; Haryadi, Rofiq Noorman (Jurnal Pengabdian Masyarakat Madani, 2024)
Sheep are livestock that require feed material in the form of large amounts of green, which is around 90%. Livestock Feed is one of the most important things for goat and sheep. Without a balance of good feed materials, growth in goat animals and sheep will slow down because the nutrients given don't match the needs. Concentrated feed or booster feed is only a portion of additional feed Concentrate is a feed that has a rough fiber content. In the process of making konsentsent, all the ingredients that have passed the milling process should be in a soft condition making it easy to mix with each other. In this study used the kulitatif method by observation and interviews with cage employees to obtain optimal results from the combination of substances on feed material. Solving for the problem is needed by comparison between livestock nutrition data with data on kosentrat livestock feed and green nature combination. This study aims to implement qualitative methods in the content of livestock feed. This study also results in an understanding that feed is an important factor in increasing livestock productivity and in Tegalsalam Farm and Feed has also had the ability to make concentrated feed materials